Análise de ministr's em impressões digitais depositadas em suportes variados - Vieira, Carolina Mayumi (2014)
The human fingerprint identification is a simple, fast and economical method. However, blurred prints deposited on rough surfaces constitute a challenge because of the loss of details. The development methods are insufficient to allow the analysis of the fingerprint, as observed points may be blurred or damaged. With the advances in DNA genotyping technology, small amounts of biological material such as a dozen cells can yield a complete DNA profile and be of great help in criminal investigations. In this context, fingerprints, previously only analyzed from the lophoscopic aspect, can now have a genetic approach. The use of MiniSTR 's combined with an increase in the number of PCR cycles can improve the detection of DNA in samples with degraded and/or limited amount of DNA. When investigating a crime scene, the forensic expert should keep in mind there is no hierarchy among evidence and every vestige should be analyzed considering its feasibility and effectiveness in generating proof.